Biological vascular age and its relationship with cardiovascular risk factors - A. A. Akopyan; I. D. Strazhesko; V. G. Klyashtorny; I. A. Orlova (Кардиоваскулярная терапия и профилактика)
Aim. To study of the relationship between cardiovascular risk factors and biological vascular age.Material and methods. The biological vascular age was estimated using models based on the arterial wall parameters. Using multiple logistic and linear regression, we studied the relationship between the biological vascular age and cardiovascular risk factors in 143 people without cardiovascular disease (CVD). Persons with a positive difference between the vascular and chronological age were assigned to the “old” vascular group, and persons with no or negative difference between the vascular and chronological age were assigned to the “young” vascular group.Results. Linear regression in the “young” vascular group showed an inverse relationship between the difference between the vascular and chronological age with the levels of low-density lipoprotein cholesterol (p=0,001; β±SE=-1,67±0,47), triglycerides (p=0,017; β±SE=-1,66±0,68), urea (p=0,025; β±SE=-0,89±0,39) and insulin resistance index (p=0,001; β±SE=-1,22±0,36). In the “old” vascular group, a direct relationship was found between the difference between the vascular and chronological age and central systolic blood pressure (p=0,015; β±SE=0,10±0,04). According to logistic regression, the likelihood of having “old” vessels increased by 1,23 times with an increase in blood glucose levels by 0,5 mmol/l (p=0,044; odds ratio (OR)=1,23; 95% confidence interval (CI): 1,011,51), the presence of hypertension (p=0,034; OR=3,11; 95% CI: 1,09-8,86) and type 2 diabetes (p=0,025; OR=3,61; 95% CI: 1,1711,09), as well as decreased by 2 times with an increase in high-density lipoprotein cholesterol by 0,3 mmol/l (p=0,003; OR=0,5; 95% CI: 0,32-0,79).Conclusion. The difference between the biological vascular age and chronological age is associated with traditional CVD risk factors.